#TITLE_ALTERNATIVE# - SYAHRUL RAMADHAN (NIM :12213072), ADNAN
As conventional oil and gas production keeps declining rapidly in Indonesia, coal bed methane (CBM) is a non-conventional energy source that needs to be studied more and more deeply, as Indonesia has a large CBM reserve potential estimated at about 6% of total reserves CBM global. Unfortunately since 2008, the production of CBM has not been satisfactory since it has not reached the target of only 1 MMSCFD. Given the enormous potential and the fact that CBM production is still low, further research should be undertaken to achieve a comprehensive understanding of this unconventional energy source. In particular, research is undertaken to investigate the reservoir of CBM Indonesia which has the potential to apply improved methods of increasing CBM (ECBM): carbon dioxide injection. A simulation study was conducted on the CBM reservoir in Sanga Sanga, Kalimantan, named Field X. The purpose of this simulation study was to find out whether Field X is a good candidate for carbon dioxide injection to increase CBM production both technically and economically, And to conduct sensitivity studies on the Injector manufacturer's well patterns, the effects of carbon dioxide injection rates on CBM gas recovery factors, the efficiency of injection and the economic value of CO2 injection projects on CBM gas production. At the end of the study, all the results of discussions and simulations gathered will draw conclusions about the potential for carbon dioxide injection to increase CBM production in Indonesia and its economic potential, as well as factors affecting recovery and injection efficiency. This comprehensive study presents a new discussion on CBM, gas characterization and reservoir, production process, ECBM method, simulation of carbon dioxide simulation injection and its economic potential especially for Indonesia.